2016
DOI: 10.9734/ejmp/2016/18826
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Antiplasmodial Activity and GC­MS Analysis of Vernonia colorata (Willd) Drake Leaf

Abstract: Aim: To analyse the phytochemical components using GC-MS technique and evaluate the antiplasmodial activity of crude extract and partitioned fractions of Vernonia colorata leaf. Study Design: Qualitative, gravimetric and Chromatographic methods of analysis were adopted for phytochemical analysis, while experimental design (In vivo) was used for antiplasmodial study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Previous work on Vernonia colorata showed an LD50 greater than 5000 mg/kg bw [6,13]. With this LD50 which is also found in the currently study, Vernonia colorata extract is practically non-toxic [14].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous work on Vernonia colorata showed an LD50 greater than 5000 mg/kg bw [6,13]. With this LD50 which is also found in the currently study, Vernonia colorata extract is practically non-toxic [14].…”
Section: Discussionsupporting
confidence: 81%
“…These results are in agreement with those of Siaka [16] except for the flavonoids which was not found in our study. Studies have shown that methanolic and ethanolic extracts of Vernonia colorata leaves contain alkaloids and flavonoids [5,7,13]. The absence of alkaloids and flavonoids in the aqueous extract could be explained by the type of extraction used and also by the existence of chemotype within the species of Vernonia colorara [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For our interviewees, the essential parameters for new diagnosis technologies reside: in the rapidity of the test: "for RDT, it lasts about 15 -20 min, on the other hand the other exams in the laboratory can last up to 5 h", "thick blood smear takes time: doctors can draw the blood in the morning and results are available in the evening, it is too long". A new method should be fast "to avoid death because if time is shorter, this implies a shorter waiting in hospital, earlier disease management so we can do something else (economic activity)" in the reliability and quality of the exams: "the actual tests are not very reliable, there are false negative results when the patient has already taken medication; in my case the RDT is always negative and the confirmation is done with the thick blood smear which is very often positive; but however Azadirachta indica A. Juss [47], Vernonia colorata (Willd) Drake [48] and Carica papaya L [49]. they still make us follow the treatment on the basis of RDT and if the condition does not improve and we return to the health center, there the doctor will prescribe a thick blood smear"; "I find that RDT is not reliable and in addition the thick blood smear can also be negative while the child has all the signs of malaria, which makes me doubt of the result"; "with RDT tests, you have to be careful because it is not exact, the test can reveal that you do not have malaria while you have it"; "the new test has to be more reliable than RDT and I want it to be a 100 % reliable test; what is new must be at least as efficient as what exists".…”
Section: Perceptions Of New Malaria Diagnostic Technologiesmentioning
confidence: 99%